Oficinas de experimentação, leitura e escrita: uma atividade social em meio à pandemia - Lustosa, Nathalia dos Santos (Universidade Federal do Tocantins, 2022)
The present work brings as a central element of reflection the experimentation as a pedagogical resource, from the reading and writing workshops in which I participated, which took place in the midst of the Covid-19 pandemic. The discussion of the theme comes from the need to understand experimentation as a methodology of the eight cycles of reading and writing workshops, organized by professors Felipe Ferreira Joaquim and Rafael Caetano do Nascimento, through extension courses at the Federal University of Tocantins - UFT. In this way, we intend to understand how to develop and execute experimentation as a pedagogical resource, in order to guarantee a better development in the teaching-learning process, in addition to stimulating reading and writing, respecting the individualities of each subject. Methodologically, the work is guided by carrying out a narrative research, based on bibliographic and documental research procedures. The starting point of the research was the experiences, lived and told in my participation in eight cycles of workshops. From them, I sought to subsidize the reflections through books and articles that address the theme of experimentation, words, reading and writing, observing aspects that allow the discussion of the proposed theme, as in the studies of Larrosa (2002) and Freire (1989) . In addition, it was possible to record the realization of the workshop cycles and reflect on them through the study of the workshop notebooks, produced by the participants of each cycle. Thus, we identified that experimentation can be used as a teaching methodology, in order to develop different dimensions of life and value the experiences and trajectories of each person in the educational process. In this way, I emphasize that holding the workshops during the pandemic period was a way to provide the pleasure of reading and writing, in addition to sharing knowledge.